Improved hydrogen sorption kinetics in Mg modified by chosen catalysts. (29th March 2019) - Cermak, Jiri; Kral, Lubomir; Roupcova, Pavla
Abstract: Hydrogen sorption characteristics were investigated in Mg modified by ten chosen catalyzing additives X = Mg2 Si, Mg2 Ge, Mg17 Al12, Mg5 Ga2, NaCl, LiCl, NaF, LiF and by two combinations Ni + Mg17 Al12 and Ni + Mg2 Si. Amorphous carbon (CB) was used as an anti-sticking component. It was found that optimum content of both X and CB was between 10 and 14 wt %. To assess the effect of X itself upon the sorption kinetics, concentration of both X and CB was fixed to about 12 wt %. The shortest desorption times t 09 (time to desorption of 90 pct of stored hydrogen) showed alloys with X = NaF, Mg2 Si, Mg2 Ge and NaCl. Careful measurements of equilibrium hydrogen pressure, p eq, at 623 K showed an increase in p eq for added chlorides, fluorides, Mg2 Ge and also for Mg2 Si. TPD experiments revealed desorption peaks for X = NaCl, LiF shifted down to temperatures as low as 597 K. Highlights: Hydrogen storage in Mg-based alloys was studied at temperatures 575-658 K. Hydrogen storage capacity of studied materials was about 6 wt. % H2 . The best desorption kinetics at 623 K ( t 09 = 1.2 min) was found for Mg-12NaF-13CB.